PARTICIPATIVE MANAGEMENT AND HUMANIZATION: A MUNICIPAL EXPERIENCE IN BRAZILIAN SEMI-ARID NORTHEAST (Fiep Bulletin - online, 2012)
It's reported the experience of building knowledge for technical training of the municipal government of São Bento do Norte/RN/Brazil, starting at the need of managers and servers for the humanized management, turned to the receptivity with solutions, strengthening the democratic and collective process for compromising. Starting with a qualitative method based on the reflection of the results produced with the participation of 66 individuals. The experiment took place in three movements, being the first described as the field study, context analysis, constructions with mayors and municipal assistants; the second being the collective construction in conversations circles with the management team and representatives of society and survey of the themes; the third a reflection and data creation. The conversation circles made possible horizontalness in the relations, made also possible articulated commitments to implement the training, as possibilities to promote changes by interactional dialogic encouraging its construction in the action, to practices that incorporate integrated policies for planning and development.
Keywords: Participatory management; Humanization; Training.